A monetary business-cycle model with an augmented cash-inadvance constraint, investment tax credit and a government sector: the case of Bulgaria (1999-2022) - Vasilev, Aleksandar (Journal of Mathematical Economics and Finance, 2023)
We modify an otherwise standard business cycle model with a richer government sector, and add an augmented cash-in-advance (CIA) considerations. In particular, the cash in advance constraint of Cole (2020) is extended to include private investment and government consumption, and allows a proportion of total expenditure to be done using credit. Additionally, we allow for the presence of an investment subsidy (“investment tax credit”). This specification is then calibrated to Bulgarian data after the introduction of the currency board (1999-2022), gives a role to money in accentuating economic fluctuations. In particular, the modified CIA constraint pro- duces a mechanism that allows the framework to reproduce better observed variability and correlations among model variables, and those characterizing the labor market in particular.